Requirement of Replication Checkpoint Protein Kinases Mec1/Rad53 for Postreplication Repair in Yeast - Venkateswarlu Gangavarapu (American Society for Microbiology, 2011)
ABSTRACT DNA lesions in the template strand block the replication fork. In Saccharomyces cerevisiae, replication through DNA lesions occurs via a Rad6/Rad18-dependent pathway where lesions can be bypassed by the action of translesion synthesis (TLS) DNA polymerases η and ζ or by Rad5-mediated template switching. An alternative Rad6/Rad18-independent but Rad52-dependent template switching pathway can also restore the continuity of the replication fork. The Mec1/Rad53-dependent replication checkpoint plays a crucial role in the maintenance of stable and functional replication forks in yeast cells with DNA damage; however, it has remained unclear which of the lesion bypass processes requires the activation of replication checkpoint-mediated fork stabilization. Here we show that postreplication repair (PRR) of newly synthesized DNA in UV-damaged yeast cells is inhibited in the absence of Mec1 and Rad53 proteins. Since TLS remains functional in cells lacking these checkpoint kinases and since template switching by the Rad5 and Rad52 pathways provides the alternative means of lesion bypass and requires Mec1/Rad53, we infer that lesion bypass by the template switching pathways occurs in conjunction with the replication fork that has been stabilized at the lesion site by the action of Mec1/Rad53-mediated replication checkpoint. IMPORTANCE Eukaryotic cells possess mechanisms called checkpoints that act to stop the cell cycle when DNA replication is halted by lesions in the template strand. Upon stalling of the ongoing replication at the lesion site, the recruitment of Mec1 and Rad53 kinases to the replication ensemble initiates the checkpoint wherein Mec1-mediated phosphorylation of Rad53 activates the pathway. A crucial role of replication checkpoint is to stabilize the replication fork by maintaining the association of DNA polymerases with the other replication components at the stall site. Our observations that Mec1 and Rad53 are required for lesion bypass by template switching have important implications for whether lesion bypass occurs in conjunction with the stalled replication ensemble or in gaps that could have been left behind the newly restarted forks. We discuss this important issue and suggest that lesion bypass in Saccharomyces cerevisiae cells occurs in conjunction with the stalled replication forks and not in gaps.